1995
DOI: 10.1007/bf02246102
|View full text |Cite
|
Sign up to set email alerts
|

Differential anti-parkinsonian effects of benzazepine D1 dopamine agonists with varying efficacies in the MPTP-treated common marmoset

Abstract: In common marmosets systemically treated with MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine), the behavioural effects of benzazepine D1 dopamine (DA) agonists with full/supramaximal (SKF 80723 and SKF 82958), partial (SKF 38393, SKF 75670 and SKF 83565) and no efficacies (SKF 83959) in stimulating adenylate cyclase (AC) activity were investigated. The benzazepine derivatives, with the exception of SKF 82958 (8 fold D1 DA receptor selectivity), demonstrated high D1 DA receptor affinity and selectivity (app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Studies performed in MPTP-lesioned monkeys are to some extent contradictory on this matter, yet most emphasize that D1/D5 agonists induce significant dyskinesia (Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000) and the D1/D5 agonist ABT-431 is as potent as levodopa in inducing dyskinesia in patients (Rascol et al, 2001). Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995). Overall, these findings are well in line with recent research showing altered D1 receptor signaling in the striatum of parkinsonian rats (Gerfen et al, 2002) and MPTP monkeys rendered dyskinetic by chronic levodopa administration (Aubert et al, 2005), and further support the usefulness of rodent models of PD for the study of dopamine agonistinduced dyskinesia.…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 91%
See 1 more Smart Citation
“…Studies performed in MPTP-lesioned monkeys are to some extent contradictory on this matter, yet most emphasize that D1/D5 agonists induce significant dyskinesia (Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000) and the D1/D5 agonist ABT-431 is as potent as levodopa in inducing dyskinesia in patients (Rascol et al, 2001). Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995). Overall, these findings are well in line with recent research showing altered D1 receptor signaling in the striatum of parkinsonian rats (Gerfen et al, 2002) and MPTP monkeys rendered dyskinetic by chronic levodopa administration (Aubert et al, 2005), and further support the usefulness of rodent models of PD for the study of dopamine agonistinduced dyskinesia.…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 91%
“…But the neural mechanisms of dopamine agonist-induced dyskinesia are thought to essentially concern the indirect pathway (Crossman, 1990;Obeso et al, 2000) and our findings suggest a primary involvement of the D1 receptor regulated direct pathway. A primary involvement of D1 receptors and the direct basal ganglia pathway is suggested by other recent studies too (Aubert et al, 2005;Fiorentini et al, 2006), and by the fact that D2 family agonists are less likely to induce dyskinesia in patients and animal models of PD than unselective and D1/D5 selective agonists (present findings; Gnanalingham et al, 1995;Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000;Nutt, 2000;Rascol et al, 2001;Lundblad et al, 2002;Monville et al, 2005). A recent study established that levodopa-induced dyskinesia in the rat 6-OHDA model is related to increased synchronization of afferent activity to the basal ganglia output nuclei (Meissner et al, 2006).…”
Section: Severity Of Fd Is Related To Striatal and Motor Cortex Bold supporting
confidence: 72%
“…It has been shown that SKF83959 produces potent antiparkinsonian effects in primate and rodent models [5][6][7] . Furthermore, SKF83959 has been reported to attenuate L-DOPAinduced dyskinesia (LID) in 6-OH-DOPA-lesioned rat models [5,8] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SKF83959 produces potent antiparkinsonian effects in primate and rodent models [5][6][7] . Furthermore, SKF83959 has been reported to attenuate L-DOPAinduced dyskinesia (LID) in 6-OH-DOPA-lesioned rat models [5,8] . Recently, SKF83959 has been shown to be an identified allosteric modulator of the sigma-1 receptor and to have antidepressant effects [9] ; moreover, SKF83959 has also been shown to improve the survival of pheochromocytoma cells (PC12 cells) subjected to H 2 O 2 insult [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation